On one modulus inequality for mappings with finite length distortion - Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
The Väisälä inequality, which is well known in the theory of quasilinear mappings, is extended to the class of mappings with finite length distortion.